Ab initio thermodynamics of complex alloys: The case of Al- and Mn-doped ferritic steels. (1st May 2019) - Besson, Rémy; Dequeker, Jérôme; Thuinet, Ludovic; Legris, Alexandre
Abstract: In the context of Al and Mn-doped ferritic steels, we progressively elaborate an atomic-scale energy model to reproduce the thermodynamic behaviour of quaternary FeAlMnC on a bcc lattice. This model is built on physical concepts: DFT calculations, pair Hamiltonians, non-configurational thermal effects, these elements being combined in a reasoned way to lead to a mastered and predictive formulation. In particular, this approach allows to explore the correlation between ordering in substitutional ternary FeAlMn and interstitial carbon, which brings new elements to the metallurgy of carbon in ferritic steels. Graphical abstract: Image 1